2000
DOI: 10.1056/nejm200005253422101
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Resuscitation by Chest Compression Alone or with Mouth-to-Mouth Ventilation

Abstract: The outcome after CPR with chest compression alone is similar to that after chest compression with mouth-to-mouth ventilation, and chest compression alone may be the preferred approach for bystanders inexperienced in CPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
215
0
17

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(245 citation statements)
references
References 11 publications
5
215
0
17
Order By: Relevance
“…Another basis of the recommendation is that conventional CPR may be associated with delayed initiation of BCPR and consequently diminished effect of BCPR, particularly when dispatchers provided DA-CPR instruction on bystanders [1,9]. This study showed that the incidence of ventilation-only BCPR decreased after implementation of the new JRC guidelines 2005 released at the end of 2006.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Another basis of the recommendation is that conventional CPR may be associated with delayed initiation of BCPR and consequently diminished effect of BCPR, particularly when dispatchers provided DA-CPR instruction on bystanders [1,9]. This study showed that the incidence of ventilation-only BCPR decreased after implementation of the new JRC guidelines 2005 released at the end of 2006.…”
Section: Discussionmentioning
confidence: 74%
“…The latter meta-analysis included prospective randomized studies that compared dispatcher-assisted compression-only CPR with conventional CPR; these randomized studies revealed the superiority of compressiononly CPR to conventional CPR [1,3]. The former meta-analyses included observational studies investigating the difference in outcomes between compression-only CPR and conventional CPR, in all OHCA having bystander CPR [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bystanders are reluctant to perform chest compression because of fear of causing harm, fear of litigation, the complexity of performing mouth‐to‐mouth rescue breathing, and the unwillingness to perform mouth‐to‐mouth contact 4, 5, 6. Bystanders’ reluctance may be due to their insufficient knowledge, skills, or confidence.…”
Section: Introductionmentioning
confidence: 99%
“…In our animal models of VF arrest, we initially found that survival was similar with CO‐CPR and guideline protocols that recommended ventilations 21, 22. Support in humans for CO‐CPR at that time was a study by Hallstrom and associates of dispatcher‐assisted CPR that found CO‐CPR was as effective as standard CPR 23. Further support came later by the important SOS‐KANTO study from Japan 14…”
Section: Resuscitation Research Led To New Approachesmentioning
confidence: 78%